Cannabinoids and cancer: potential for colorectal cancer therapy. (1st August 2005) - Patsos, H.A.; Hicks, D.J.; Greenhough, A.; Williams, A.C.; Paraskeva, C.
Abstract : Despite extensive research into the biology of CRC (colorectal cancer), and recent advances in surgical techniques and chemotherapy, CRC continues to be a major cause of death throughout the world. Therefore it is important to develop novel chemopreventive/chemotherapeutic agents for CRC. Cannabinoids are a class of compounds that are currently used in the treatment of chemotherapy-induced nausea and vomiting, and in the stimulation of appetite. However, there is accumulating evidence that they could also be useful for the inhibition of tumour cell growth by modulating key survival signalling pathways. The chemotherapeutic potential for plant-derived and endogenous cannabinoids in CRC therapy is reviewed.